Disaster preparedness in universities - Jaradat, Ahmad; Mziu, Hadjar; Ibrahim, Jamaludin (IJCTT Journal, 2015)
Although the awareness of disasters has increased among some parts of society, the concept of disaster preparedness and response has not been sufficiently explored in universities. The aim of this paper is to assess the perceptions of students and staff regarding disaster preparedness as well as to examine whether universities are prepared for disasters or not. In addition, this article provides a brief overview of major disasters that happened to universities in the past years in order to analyse the implications of disasters to universities. Furthermore, the stakeholders involved in disaster management are mentioned here followed by a general plan and recommendations for universities to be considered in their roles toward building a resistant university.